-(x-1)=2+(2x+5)

Simple and best practice solution for -(x-1)=2+(2x+5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(x-1)=2+(2x+5) equation:


Simplifying
-1(x + -1) = 2 + (2x + 5)

Reorder the terms:
-1(-1 + x) = 2 + (2x + 5)
(-1 * -1 + x * -1) = 2 + (2x + 5)
(1 + -1x) = 2 + (2x + 5)

Reorder the terms:
1 + -1x = 2 + (5 + 2x)

Remove parenthesis around (5 + 2x)
1 + -1x = 2 + 5 + 2x

Combine like terms: 2 + 5 = 7
1 + -1x = 7 + 2x

Solving
1 + -1x = 7 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
1 + -1x + -2x = 7 + 2x + -2x

Combine like terms: -1x + -2x = -3x
1 + -3x = 7 + 2x + -2x

Combine like terms: 2x + -2x = 0
1 + -3x = 7 + 0
1 + -3x = 7

Add '-1' to each side of the equation.
1 + -1 + -3x = 7 + -1

Combine like terms: 1 + -1 = 0
0 + -3x = 7 + -1
-3x = 7 + -1

Combine like terms: 7 + -1 = 6
-3x = 6

Divide each side by '-3'.
x = -2

Simplifying
x = -2

See similar equations:

| -5.61-0.1y=0.1y | | 5+.75x=7.25+.35x | | 19x+7=900 | | 25+.25=35+10x | | 3(2c-3)=15 | | 3(k+3)=6 | | 17x-11=720 | | 5x+9=-12x-5 | | 4(d-2)=8 | | 3x(2x-1)=4-(7x+9) | | 4(X+8)=12 | | 15-2(x-2)= | | 3+(2x-1)=4-(7x+9) | | 13x+19=500 | | 516=33g | | x+2x-7=3x+7 | | -(u-9)+1=4 | | a-0.13=0.58 | | 11x-16=270 | | 5+4X=X+8 | | 14a+(-93)=49+(-57a) | | 9x+12=192 | | 10-5x=-14+(4-x) | | 5*8x= | | -8=-2-x/2 | | 8x-3=141 | | -16x-(-18)= | | 7x-12x+7= | | 7x+43=386 | | x-5+9x=2x-6+5 | | 11m+5n-2m+9n= | | 6x-31=77 |

Equations solver categories